Publication of a Church Metrics Fragment (1705–1710) Which Is Part of the Oldest Remaining Original Stakliškiai Church Baptism Metrics Dated 1705–1726 - Kaminskas-Krinčius, Algimantas (Bibliotheca Lituana, 2012)
Transcriptions of the Stakliškiai church metrics can be found dated from 1699 to 1798 while originals are available from 1705 to modern times. The article presents a church metrics fragment (1705–1710) which is part of the oldest remaining original Stakliškiai church baptism metrics dated 1705–1726. This period was chosen because in 1710 the plague made fundamental changes in the demographic situation of the town and other neighboring settlements. The main aim of the publication is to present the text not only semantically but also graphically. The entries are ordered this way: first column – the day, second column – name of the town, third column – the year, month and the whole text of the entry: name of the baptized baby, names of the parents, names of the godparents, area information and other additional notes e.g. information on the nobility of those present at the ceremony. The presented fragment is not only important to researchers of the specific town and area but also could serve as an example for preparing and researching other metrics books. Metrics books are important not only to genealogy researches but also to researchers of local history and specialists of demographics, linguistics or religious sciences.
Keywords: none